Small Bowel Obstruction Masquerading as Acute ST Elevation Myocardial Infarction - Manan Parikh; Martin Miguel Amor; Isha Verma; Jeffrey Osofsky; Madhu Paladugu (Case Reports in Cardiology)
ST segment elevation on EKG remains among the most important presentations of acute myocardial infarction. Due to the urgency of intervention for this finding, other clinical scenarios causing ST elevations on EKG may sometimes go unaddressed and can lead to fatal complications. We present a case of an 86-year-old male presenting with small bowel obstruction leading to EKG findings of ST segment elevation in the absence of critical coronary obstruction. The EKG finding resolved after the improvement of small bowel obstruction reflecting the reversible cause of the changes.